Statistics for health policy and administration using Microsoft Excel - James E. Veney (Jossey-Bass, 2003)
Statistics for Health Policy and Administration Using Microsoft Excel provides an introduction to the use of statistics in health policy and health administration-related fields. The book is keyed to the powerful statistical tool Microsoft Excel and shows how to prepare data and understand the data display capabilities of the program. It also offers the information needed to master probability the foundation of statistical analysis. This important book is structured around illustrative examples that are demonstrated with Excel displays. The book is filled with step-by-step discussions of how statistical problems are solved using Excel, and it contains a wealth of exercises addressing the material covered in each section. Many of the book's exercises include the replication of examples so that the student has an immediate reference with which to compare his or her work and determine whether or not the procedure was carried out correctly. Additional exercises are provided for further practice to reinforce the valuable lessons learned